Human Emotion Surveillance Using Computer Vision - R.Radha, Dr.; M, Atchatha.; B, Kaushik.; Felix A, Agassi; Staflin Betzy, G. (International Journal of Engineering and Technology, 2018)
India, a land of marvels, is outstanding in many aspects, its culture, ecosystem, etc. Sadly, it also ranks among the top countries in the world to have an annual suicide rate. This project aims at the foundation of human emotion surveillance.Â This system assists in the facial recognition, feature extraction and the threshold detection of stress for emotions expressed through face using the viola-jones algorithms and weak classifiers.Â This focuses basically on segregation of positive and negative emotions, detecting stress based on a usual threshold value and possibly providing an alternate means to let loose the extra stress built up if possible.Â Â